Comparative analysis of barren solution cyanide treatments with hydrogen peroxide and sodium meta-bisulfite for compliance with the Maximum Permissible Limits of mining effluents - García Girón, Arturo (2022)
The present study had the objective of determine the best treatment option of cyanide of barren solution (as known as poor solution) coming from the Process Plant of El Toro Mining Unit, in order to accomplish the quality established in the current environmental regulations. For this, the research was carried out using two treatment proposals: destruction with hydrogen peroxide and destruction with sodium metabisulfite. To conclude, sodium metabisulfite had a faster reaction and effective compared to hydrogen peroxide, obtaining the expected values ​​below the Maximum Permissible Limits (current national laws such the Supreme Decret N°010-2010-MINAM) related to total cyanide. In addition, it was determined that although the commercial cost of hydrogen peroxide (S / .3707 / Kg) is lower than sodium metabisulfite (S / .5296 / Kg); in the tests it observed that consume of hydrogen peroxide must be higher to achieve a better reduction of cyanide for the quality of the sample analyzed.